Influence of different heat-affected zone microstructures on the stress corrosion behavior and mechanism of high-strength low-alloy steel in a sulfurated marine atmosphere - Wu, Wei; Liu, Zhiyong; Li, Xiaogang; Du, Cuiwei; Cui, Zhongyu (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2019)
The stress corrosion cracking (SCC) behavior and mechanism of the simulated heat-affected zone (HAZ) of high-strength low-alloy (HSLA) steel in a sulfurated marine atmosphere were surveyed in detail using electrochemical measurements and slow strain rate tensile (SSRT) tests combined with microstructure analysis. The SCC of the simulated HAZs is controlled by both anodic dissolution (AD) and hydrogen embrittlement (HE), which are attributed to the synergistic effect of Cl− and SO42−, as Cl−-induced localized dissolution causes microcrack initiation, and SO42--catalyzed acid regeneration facilitates microcrack propagation. The intercritical HAZ and fine-grained HAZ present high crack numbers because of the high amount of prior austenite grain boundaries (PAGBs), lath bainite boundaries (LBBs), and martensite/austenite (M/A) constituents, which act as preferential sites for hydrogen trapping and crack initiation. However, coarse-grained HAZ exhibits the highest SCC susceptibility because of the coarse PAGBs, wide lath bainites (LBs), and high local dislocation density, which promote crack propagation.